Factors of Complications in Patients Undergone Tonsillectomy in Chai Nat Hospital - Gasigij, Grongthong (Journal of Health Science of Thailand, 2018)
This prospective descriptive study was aimed at defining factors of complications in 54 patients undergone tonsillectomy in Chai Nat Hospital, between 1 December 2006 and 31 December 2008. Their age, sex, indication for tonsillectomy, post operative complications, treatment process (pre- operative, intra-operative and post-operative) were analyzed. It was found that their ages ranged from 2 to 48 years with the mean of 25 years. Most of them were 0-9 years old (35.2%) showing indication for tonsillectomy of chronic tonsillitis (48.2%), tonsillar hypertrophy with snoring (38.8%), halitosis (9.3%) and having history of peritonsillar abscess (3.7%). All patients were inducted under general anesthesia, tonsil was dissected from upper pole to lower pole of tonsil and tonsil was removed by snare technique, then bleeding control by monopolar electrical cauterization or loop ligation for large size artery. Before dissected, 1% xylocaine with adrenaline was infiltrated into surgery site, fentanyl 1-2 microgram/kg had been used for premedication during anesthesia. The most complications found were oral bleeding (4 patients) and 1 patient had symptom of upper airway obstruction. Information of patients with complications were analyzed. Many factors might influence complications of tonsillectomy,including patient status, underlying diseases,size and fribrosis of tonsils,duration of surgery and post operative care. The results showed that complications might occur in any step of management. Effective surveillance of cases through surgery and pre - post operative care is strongly recommended to control undue complications.